THE PROBLEM OF CLASSIFICATION OF HISTORICAL MONUMENTS IN ALGERIA: THE CASE OF THE AGHA PALACE IN FERDJIOUA - Mme Souki; Chabi Nadia (International Journal of Innovative Technologies in Social Science, 2024)
Algeria has a rich cultural heritage, but the heritage classification process is still flawed. There are indeed historical monuments that have benefited from the classification process, but in reality have been neglected, such as the Agha Palace in Ferdjioua. The reflection focuses on this type of classified monuments, highlighting the importance of heritage enhancement in Algeria. We try to compare the current state of the monument with the effects normally induced by the procedure of its classification, in order to detect incompatibilities in the process of its patrimonialisation. In order to propose a revaluation of the palace through a new strategic vision of its conservation, this monument must be able to acquire an economic value and a social role with a significant impact, ensuring its sustainability by associating the user with the value of the most appropriate use.